Facial Scar Revision by Using Fractional CO2 Laser - Abdul Sattar Sami; Balsam Saadi; Ehab Safauldeen Abdulwahhab (Academic Journal of Clinicians, 2024)
Background: Facial scar is the normal resultant of the surgical correction, trauma and infection which is of great challenge for both the patient and the surgeon, in that affect the psychology and aesthetic, as well as, the surgeon to minimize the scar effect or at least hide it. Fractional CO2 laser with 10600 nm wave length, highly absorbed by the most skin constituents (water molecule) is effective with precise ablation with minimum injury to the unwanted area. Objective: To evaluate the efficacy of ablative fractional CO2 laser in facial scar revision and to get better aesthetic and form of facial scar. Patients and methods: In this study 26 patient with facial scar (12 males,14 female) receive 3 sessions of 2-3 weeks’ interval. Fractional CO2 laser with 10600 nm wavelength ,7 articulated arm with scanner hand piece, 20 watts, 4 times scan with 1 millisecond duration and 1 millimeter distance among pixels. Results: patient satisfaction/7 patients (27%) good outcome, and only 4 patients (15%) with excellent outcome,8 patients (31%) express poor outcome, 7 patients (27%) fair outcome according to patient satisfaction, operator satisfaction/ good outcome in 6 patients (23%), and only 1 patient (4%) with excellent outcome satisfy poorly in 9 patients (34.5%), fairly in 10 patients (38.5%). Conclusion: Utilizing a CO2 laser, ablative fractional resurfacing allows for the precise removal and cauterization of deep layers of the skin, while reducing the recovery time for patients and minimizing the likelihood of severe side effects.